Adipogenic Differentiation of hMSCs is Mediated by Recruitment of IGF‐1r Onto the Primary Cilium Associated With Cilia Elongation. (June 2015) - Dalbay, Melis T.; Thorpe, Stephen D.; Connelly, John T.; Chapple, J. Paul; Knight, Martin M.
Abstract Primary cilia are single non‐motile organelles that provide a highly regulated compartment into which specific proteins are trafficked as a critical part of various signaling pathways. The absence of primary cilia has been shown to prevent differentiation of human mesenchymal stem cells (hMSCs). Changes in primary cilia length are crucial for regulating signaling events; however it is not known how alterations in cilia structure relate to differentiation. This study tested the hypothesis that changes in primary cilia structure are required for stem cell differentiation. hMSCs expressed primary cilia that were labeled with acetylated alpha tubulin and visualized by confocal microscopy. Chemically induced differentiation resulted in lineage specific changes in cilia length and prevalence which were independent of cell cycle. In particular, adipogenic differentiation resulted in cilia elongation associated with the presence of dexamethasone, while insulin had an inhibitory effect on cilia length. Over a 7‐day time course, adipogenic differentiation media resulted in cilia elongation within 2 days followed by increased nuclear PPARγ levels; an early marker of adipogenesis. Cilia elongation was associated with increased trafficking of insulin‐like growth factor‐1 receptor β (IGF‐1Rβ) into the cilium. This was reversed on inhibition of elongation by IFT‐88 siRNA transfection, which also decreased nuclear PPARγ. This is the first study to show that adipogenic differentiation requires primary cilia elongation associated with the recruitment of IGF‐1Rβ onto the cilium. This study may lead to the development of cilia‐targeted therapies for controlling adipogenic differentiation and associated conditions such as obesity. Stem Cells2015;33:1952–1961